2020
DOI: 10.3354/meps13417
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Atlantidae species (Gastropoda: Pterotracheoidea) during an El Niño event in the Southern California Current System (summer-fall 2015)

Abstract: Atlantids are holoplanktonic gastropods present in tropical to sub-polar waters, and have gained an increasing interest due to their potential use as biological indicators of climate change and ocean acidification. However, there is a lack of information regarding their distribution for large areas of some oceans, particularly in the California Current System (CCS), which has been used as a model for many acidification studies and where intense warming events occur. The distribution patterns of 18 species of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…A relatively high planktonic gastropod diversity was observed in the present study as compared to that found in 2 sites of the Caribbean Sea: 31 species (Oliva-Rivera & Navarrete, 2007) and 34 species (Chávez-Villegas et al, 2014), but lower than the 62 holoplanktonic species from the Gulf of California (Angulo-Campillo et al, 2011), the 6 species of the order Thecosomata (Sánchez-Hidalgo y Anda, 1989), and the 18 species of the family Atlantidae off the BCP (Aceves-Medina et al, 2020;Moreno-Alcántara et al, 2020). Nevertheless, according to a preliminary rarefaction analysis (results not shown due to reduced sample size) the actual species diversity in our study region is probably under-represented.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…A relatively high planktonic gastropod diversity was observed in the present study as compared to that found in 2 sites of the Caribbean Sea: 31 species (Oliva-Rivera & Navarrete, 2007) and 34 species (Chávez-Villegas et al, 2014), but lower than the 62 holoplanktonic species from the Gulf of California (Angulo-Campillo et al, 2011), the 6 species of the order Thecosomata (Sánchez-Hidalgo y Anda, 1989), and the 18 species of the family Atlantidae off the BCP (Aceves-Medina et al, 2020;Moreno-Alcántara et al, 2020). Nevertheless, according to a preliminary rarefaction analysis (results not shown due to reduced sample size) the actual species diversity in our study region is probably under-represented.…”
Section: Discussioncontrasting
confidence: 49%
“…Planktonic dispersal in the marine environment is one of the leading connectivity processes among populations of meroplanktonic and holoplanktonic gastropods (Crocetta et al, 2020;Roegner, 2000), and is a relevant element of the trophic dynamics of ecosystems and indirect indicators of the health of adult populations (Campos & Landaeta, 2016;Chávez-Villegas et al, 2014). Planktonic dispersal study will aid in a better understanding of the molluskan community's behavior under present and future environmental conditions (e.g., Aceves-Medina et al, 2020;Molina-González et al, 2018). For this purpose, baseline studies on the species composition that rely on the use of genetic markers are a starting point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation